2018
DOI: 10.3324/haematol.2017.176123
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of metabolic syndrome in adults from the French childhood leukemia survivors’ cohort: a comparison with controls from the French population

Abstract: The prevalence of the metabolic syndrome among adults from the French LEA childhood acute leukemia survivors’ cohort was prospectively evaluated considering the type of anti-leukemic treatment received, and compared with that of controls. The metabolic profile of these patients was compared with that of controls. A total of 3203 patients from a French volunteer cohort were age- and sex-matched 3:1 to 1025 leukemia survivors (in both cohorts, mean age: 24.4 years; females: 51%). Metabolic syndrome was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 50 publications
8
29
0
Order By: Relevance
“…Acute lymphoblastic leukaemia (ALL) is the most common childhood cancer [7]. Advances in treatment strategies have lead to high cure rates [8], but survivors of childhood cancer are at risk of developing many therapy-related late effects, such as metabolic syndrome, cardiovascular disease and musculoskeletal disorders, later in their life [9][10][11]. In a recent cross-sectional study of young adult survivors of childhood ALL (median age = 26 years old) with a median period of 18.5 years off-chemotherapy, we reported reduced gut microbiota diversity and distinct gut microbiota profile as compared to controls who had no history of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute lymphoblastic leukaemia (ALL) is the most common childhood cancer [7]. Advances in treatment strategies have lead to high cure rates [8], but survivors of childhood cancer are at risk of developing many therapy-related late effects, such as metabolic syndrome, cardiovascular disease and musculoskeletal disorders, later in their life [9][10][11]. In a recent cross-sectional study of young adult survivors of childhood ALL (median age = 26 years old) with a median period of 18.5 years off-chemotherapy, we reported reduced gut microbiota diversity and distinct gut microbiota profile as compared to controls who had no history of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear if the microbiota diversity observed in these young adult survivors of ALL is a consequence of chemotherapy exposure during their childhood and has in fact, persisted over time. Understanding this is particularly important in the context of late effects in childhood cancer survivors, which include gastrointestinal complications, chronic inflammation, metabolic syndrome, and cardiovascular disease [9,10,13,14]; conditions, which have all been, associated with gut dysbiosis in the general population [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…cohort showed that the prevalence of metabolic syndrome was increased among childhood leukemia survivors, relative to controls; risk was greatest, however, among those transplanted with TBI (OR 6.26, 95% CI, 4.17–9.36; p < 0.001) followed by those treated with chemotherapy and cranial radiation (OR 2.32, 95% CI, 1.36–3.97; p = 0.002), transplantation without radiation (OR 2.18, 95% CI, 0.97–4.86; p = 0.057), and chemotherapy alone (OR 1.68, 95% CI, 1.17–2.41; p = 0.005). Interestingly, metabolic syndrome presentation differed based on exposure history; when compared to controls, cranial radiation recipients with metabolic syndrome had a larger waist circumference relative to controls (109 vs. 99.6 cm; p = 0.007), while TBI recipients had a smaller waist circumference (91 vs. 99.6 cm; p = 0.01) as well as increased triglyceride levels, fasting glucose levels, and systolic blood pressure [78]. These differences likely reflect divergent pathophysiology of metabolic syndrome after different treatment exposures; further work is needed to elucidate the mechanisms underlying these noted discrepancies.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Various factors contribute to metabolic abnormalities after AL treatment: growth hormone deficiency (7), chronic inflammation (8), nutritional deficiencies, gut microbiome, endothelial dysfunction (9) and irradiation (6, 10, 11, 12). Several studies have demonstrated that total body irradiation (TBI), given as a conditioning regimen before hematopoietic stem-cell transplantation, represents a major risk factor for developing MS and CVD (10, 11, 12, 13, 14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, even among survivors with MS, patients who received TBI for AL are leaner than those who did not (16). We have recently shown in a cohort of 1025 leukemia survivors that irradiated patients had a particular profile of MS with significantly more pronounced insulin resistance parameters (higher triglycerides, higher plasma glucose levels and lower HDL-C levels) despite lower BMIs and lower waist circumferences when compared to controls (15).…”
Section: Introductionmentioning
confidence: 99%